Weekend warrior exercise model for protection from chronic mild stress‑induced depression and ongoing cognitive impairment - ŞAHİN, ALİ (My University, 2023)
We aim to investigate the role and biological mechanisms of the weekend warrior (WW) exercise model on depression‑induced rats in comparison to the continuous exercise (CE) model. Sedentary, WW, and CE rats were subjected to chronic mild stress (CMS) procedure. CMS and exercise protocols continued for six weeks. Anhedonia was evaluated by sucrose preference, depressive behavior by Porsolt, cognitive functions by object recognition and passive avoidance, and anxiety levels by open field and elevated plus maze. After behavioral assessments, brain tissue myeloperoxidase (MPO) activity, malondialdehyde (MDA) levels, superoxide dismutase and catalase activities and GSH content, tumor necrosis factor‑α (TNF‑α), interleukin‑6 (IL‑6), IL‑1β, cortisol and brain‑derived neurotrophic factor levels and histological damage was assessed. CMS‑induced depression‑like outcomes with increases in anhedonia and decreases in cognitive measures that are rescued with both exercise models. The increased immobilization time in the Porsolt test was decreased with only WW. Exercise also normalized the suppression of antioxidant capacity and MPO increase induced by CMS in both exercise models. MDA levels also declined with both exercise models. Anxiety‑like behavior, cortisol levels, and histological damage scores were exacerbated with depression and improved by both exercise models. TNF‑α levels were depleted with both exercise models, and IL‑6 only with WW. WW was as protective as CE in CMS‑induced depression‑like cognitive and behavioral changes via suppressing inflammatory processes and improving antioxidant capacity.
Keywords: weekend warrior; exercise; depression; cognitive function; continuous exercise